Turkish EFL Instructors’ Perception of Culture and Intercultural Competence in ELT - Akdemir, Ufuk (My University, 2017)
In Turkey recently, English has been the most dominant foreign language. It is simply due to the fact that English plays a key role in politics, technology and the global economy. English has become so important that in certain universities in Turkey, even the medium of instruction is English, meaning the studies are in English. If students who are to attend these universities do not have a certain level of proficiency in English, it is compulsory for them to attend a one-year intensive English course at English preparatory schools. At these preparatory schools, while English has been taught, the relationship between culture and intercultural competence has always been open to discussion. It can even be said that the lack of sensitivity to culture and intercultural competence has been the case. To understand this issue, it is crucial to know the opinions of instructors teaching English. In this regard, it has been aimed to discover EFL instructors’ perception of culture and intercultural competence in this study. Furthermore, it is conducted as a case study, meaning only an English preparatory school at one specific university. In this study, data have been gathered and analyzed in two forms: quantitative and qualitative. The quantitative data have been analyzed by calculating mean scores as Sercu (2005) suggests in her study. In addition, for the qualitative data, content analysis has been applied to the interviews to make meaningful interpretations about the instructors’ ideas about this topic. Quantitative findings have indicated that the instructors present a positive attitude towards integrating culture and intercultural competence into teaching English, and make use of a variety of activities in their classes. Additionally, qualitative findings have revealed that the instructors have a considerably high level of awareness about culture and intercultural competence in English language teaching although there is no direct link to them in the objectives.
Keywords: culture; intercultural competence; intercultural communication; English as a foreign language; English language teaching; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|